2001
DOI: 10.1046/j.1365-2044.2001.02139.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of xenon as a potential cardiostable sedative: a comparison with propofol after cardiac surgery

Abstract: SummaryXenon anaesthesia is thought to have minimal haemodynamic side-effects. It is, however, expensive and requires special delivery systems for economic use. In this randomised cross-over study, we: (i) investigated the haemodynamic profile and recovery characteristics of xenon compared with propofol sedation in postoperative cardiac surgery patients, and (ii) evaluated a fully closed breathing system to minimise xenon consumption. We demonstrated a significantly faster recovery from xenon (3 min 11 s) than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 19 publications
(18 reference statements)
3
35
0
2
Order By: Relevance
“…Xenon is also attractive in this role because of its lack of chemical reactivity and lack of clinical side effects (Dingley et al, 2001;Marx et al, 1997;Preckel et al, 2004;Rossaint et al, 2003), rapid reversibility, and lack of fetotoxicity (Burov et al, 2002;Lane et al, 1980). A radioisotope of Xe (Xe 133 ) has been used in neonates by injecting Xe 133 dissolved in 1 ml of water and counting the distribution of radioactivity as a measure of blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…Xenon is also attractive in this role because of its lack of chemical reactivity and lack of clinical side effects (Dingley et al, 2001;Marx et al, 1997;Preckel et al, 2004;Rossaint et al, 2003), rapid reversibility, and lack of fetotoxicity (Burov et al, 2002;Lane et al, 1980). A radioisotope of Xe (Xe 133 ) has been used in neonates by injecting Xe 133 dissolved in 1 ml of water and counting the distribution of radioactivity as a measure of blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, no studies have examined the effects of anaesthetic concentrations of xenon in patients with known cardiac disease. Because previous studies have revealed minimal cardiovascular effects of xenon [3,9,10], we hypothesised that xenon at an anaesthetic concentration would provide haemodynamic stability in patients with ischaemic heart disease. Therefore, we compared the haemodynamic effects of 60% xenon and N 2 O using a TOE and a pulmonary artery catheter in patients due to undergo coronary artery bypass graft (CABG) surgery.…”
mentioning
confidence: 99%
“…One study was performed in healthy surgical patients [3]. In two other studies performed by the same investigators [9,10], xenon was used at an average concentration of only 27-28% to produce sedation but not anaesthesia (the minimum alveolar concentration [MAC] of xenon is 71% [11]). To the best of our knowledge, no studies have examined the effects of anaesthetic concentrations of xenon in patients with known cardiac disease.…”
mentioning
confidence: 99%
“…Xenon, a noble gas with anesthetic properties, has shown great promise as a neuroprotectant in both in vitro and in vivo experimental studies. 14 -20 It is attractive as a combination therapy with hypothermia owing to its lack of chemical reactivity, lack of clinical side effects, [21][22][23][24] previous use in neonates, 25 rapid reversibility, and lack of fetotoxicity. 26,27 Furthermore, xenon was approved as an anesthetic drug in Russia in 2002, 28 in Germany in 2005, and extended through Europe in March 2007.…”
mentioning
confidence: 99%